Postprandial lipemia 16 and 40 hours after low-volume eccentric resistance exercise - Pafili, Z.K.a b , Bogdanis, G.C.a , Tsetsonis, N.V.a , Maridaki, M.a (Medicine and Science in Sports and Exercise, 2009)
PURPOSE: There is evidence to suggest that muscle damage caused by resistance exercise (RE) may increase postprandial lipemia (PPL). This study examined PPL for two consecutive days after a protocol of low-volume eccentric RE that caused muscle damage. METHODS: Nine healthy, untrained male volunteers aged 27.2 ± 1.1 yr performed a session of eccentric RE consisting of eight sets of inclined leg presses at six repetition maximum with 3-min rest intervals. A high-fat meal (1.2 g fat, 1.2 g carbohydrate, 0.22 g protein, and 68.6 kJ•kg -1 body mass) was administered 16 h (day 1) and 40 h (day 2) after exercise as well as after an overnight fast with no prior exercise (control condition [C]). Venous blood samples were obtained before and hourly for 6 h after each meal. RESULTS: The duration of the exercise session (including rest intervals) was 25.6 ± 0.2 min, whereas net exercise time was 4.6 ± 0.2 min. Total energy expenditure was 0.64 ± 0.04 MJ. Serum creatine kinase and ratings of perceived muscle soreness were significantly elevated on day 1 and peaked on day 2. Triacylglycerol total area under the curve was 12.1% lower on day 1 compared with C (7.51 ± 0.99 vs. 8.54 ± 1.07 mmol•L -1•6 h -1, P < 0.02), whereas no difference existed between C and day 2. Serum insulin incremental area under the curve was significantly elevated on day 2 compared with C, indicating transient insulin resistance. CONCLUSION: These results show that low-volume eccentric RE is effective in reducing postprandial triacylglycerol concentration despite the low energy expenditure. Muscle damage does not have a detrimental effect on PPL. © 2009 by the American College of Sports Medicine.